Modeling of Degenerative-Dystrophic Changes in the Lumbar Spine Intervertebral Disc in Experiment - O. A. Goldberg; A. P. Zhivotenko; V. A. Sorokovikov; Z. V. Koshkareva (Acta Biomedica Scientifica, 2019)
The paper presents an experimental model of the development of degenerative-dystrophic processes in the intervertebral disc at LVI - St level, worked out by specialists of Irkutsk Scientific Centre of Surgery and Traumatology. For the purposes of the research we used the techniques of laminectomy and LVI facetectomy.Materials and methods. The experiment was conducted on ten Wistar male rats using microsurgical instruments and binocular optics with a 6-fold magnification. The reliability and effectiveness of the obtained model were evaluated by X-ray and histological research methods. Spondylograms assessed the level, volume of surgical intervention and the likelihood of LVI spondylolisthesis occurrence relative to St against the background of impaired spinal support function created surgically on the day 15 of the experiment. The histological picture of degenerative changes in the intervertebral disc was assessed on the week 16 and 24 after the animals were sacrificed.Results. An X-ray examination on the day 15 revealed LVI spondylolisthesis relative to SI in 4 out of 10 experimental animals. To assess the nature of degenerative-dystrophic changes in the intervertebral disc, five rats were sacrificed at the 16th week and five - at the 24th week. When analyzing the obtained histological data, we noted the progression of degenerative-dystrophic changes in the intervertebral disc occurring by the 24th week.Conclusion. The designed model for the development of degenerative-dystrophic changes in the intervertebral disc is in direct correlation with the violation of the integrity of the posterior supporting complex with the subsequent formation of spondylolisthesis and instability in this segment. Histological studies in the intervertebral disc reliably confirmed the formation and progression of degenerative-dystrophic changes in the intervertebral disc at the LVI-SI level from the 16th to the 24th week of the experiment. The obtained experimental model of the formation of degenerative-dystrophic changes without mechanical damage to the intervertebral disc will allow clinicians to obtain information about the primary changes in the intervertebral disc, to study the mechanisms of development and the course of degenerative changes in the intervertebral disc on the model of disturbance of the back supporting complex with pathological changes in the biomechanics of the spine after laminectomy and facetectomy. Understanding and knowledge of the pathogenesis of degenerative-dystrophic disease of the spine will allow specialists to exercise an etiopathogenically reasonably approach to the issues of prevention and treatment.